Repetition mechanism and its impact in architectural form perception - Al-Khafaji, Ali Mohsen; Ridah, Mayce Aziz (Iraqi Journal of Architecture and Planning, 2018)
Repetition appeared in some architectural studies as a mechanism design aiming at either hiding the repeated item from the consumer, or emphasizing it. That created a query about the nature of repetition and its characteristics that change the item from being invisible to being emphasized. Moreover, the problem of the research emerged as: "the lack of perception of repetition as a mechanism of invisibility that enables the architectural form to either appear or disappear, in the consumer’s awareness." The research was divided into four stages, the first of which is introduced meaning of the main terms in the research (which are repetition, visibility and invisibility); The second, presenting the architectural studies that take relationship among those terms to reach an understanding of the technique and its limitations. Acomprehensive analysis of these studies was given in the third part to classify the information presented in them according to distance, the ratio of the length and the width of the repeated items, repetition type, the number of repeated elements, as well as the length of time the consumer is exposed to the item. In addition to that, a number of other general factors were analysed; these factors (like camouflage colouring, lighting, and chaos) affect the perception of objects. These are applied on two selected samples in the fourth part according to certain standards to reach the final results and conclusions to clarify the characteristics of repetition and help the designer to understand it and, thus, achieve invisibility or visibility. Â